Подождите немного. Документ загружается.
C
n
0
U = 0 C = n
0
n(x, y, z) = n
0
e
−U(x,y,z)/kT
.
C
n(x, y, z) dV
dV x y z
n(x, y, z) V
N
C =
N
Z
V
e
−U/kT
dV
.
n
1
n
2
n
1
n
2
= e
−(U
1
−U
2
)/kT
,
U
1
U
2
C
z
~
F = m~g ~g
z
U(z) = mgz U = 0
z = 0
n(z) p(z)
kT
U(z)
kT
=
mgz
kT
=
µgz
RT
,
µ = N
A
m R = kN
A
p(z) = p(z = 0) e
−µgz/RT
,
hvi
h1/vi
1
v
=
r
2m
kT
=
4
πhvi
.
δN(ε) ε ε + dε
ε v ε = mv
2
/2
δN(ε) = 2πN (πkT )
−3/2
√
ε e
−ε/kT
dε.
τ
τ =
1
N
N
X
i=1
τ
i
,
N 1
τ
i
N
N τ
i
i
τ
τ
z =
1
τ
,
λ = hviτ,
τ z λ
λ
d
d
σ = πd
2
.
σ
A
A
λ
σ λ
A
n λ σ ≈ 1,
n
λ ≈
1
σn
.
λ
λ =
1
√
2σn
=
0, 707
σn
.
√
2
T = 0
o
C ≈ 273 K p = 1 ≈ 10
5
n = p/kT ≈ 3 · 10
25 −3
σ ≈ 10
−19 2
λ ≈ 3 ·10
−7
= 3 · 10
−5
.
d ≈ 10
−10
λ/d ≈ 10
3
τ ≈
1
hvinσ
,
z ≈ hvinσ.
hvi =
s
8RT
πµ
,
k/m = R/µ
2
µ = 32 ·10
−3
/ T = 273 K
hvi ≈ 500 / .
τ ≈ 10
−9
, z ≈ 10
9 −1
.
d
d
1 = 10
−8
= 10
−10
l
i j = 1, 2, . . . , l
z
i
i z
ij
j
z
i
=
l
X
j=1
z
ij
,
z
ij
hvi A
z
ij
hvi → hv
i
i
n
A n
j
σ A
i
j
σ
ij
= π
r
i
+ r
j
2
,
r
i
r
j
i j σ
ij
= σ
ji
z
ij
= hv
i
iσ
ij
n
j
.
i
z
i
= hv
i
i
l
X
j=1
σ
ij
n
j
.
τ
i
i
τ
i
= z
−1
i
λ
i
= hv
i
iτ
i
= hv
i
i/z
i
λ
i
=
1
X
j
σ
ij
n
j
.
λ
1
=
1
σ
11
n
1
+ σ
12
n
2
, λ
2
=
1
σ
21
n
1
+ σ
22
n
2
,
σ
12
= σ
21
λ
i
λ
1
=
1
√
2σ
11
n
1
+ σ
12
n
2
p
1 + m
1
/m
2
,
λ
2
=
1
σ
21
n
1
p
1 + m
2
/m
1
+
√
2σ
22
n
2
,
m
1
m
2
n
1
n
2
m
1
m
2
λ
1
≈
1
√
2σ
11
n
1
+ σ
12
n
2
, λ
2
≈
p
m
1
/m
2
σ
21
n
1
.
λ
2
λ
1
n
0
n
0
n
0
(~r, t)
~r t
n
0
(x) x
dn
0
/dx J
x
x
1/
2
· J
x
n
0
= const
dn
0
/dx
n
0
x
J
x
= −D
dn
0
dx
.
D
S
x
n
0
S
τ
0
J
x
=
N
0
+
− N
0
−
τ
0
S
,
N
0
+
S τ
0
x N
0
−
x N
0
+
N
0
−
hv
0
i
1/6
x
N
0
+
n
0
x − λ
0
N
0
−
x − λ
0
λ
0
τ
0
S
λ
0
λ
0
N
0
+
=
1
6
hv
0
iτ
0
S n
0
(x −λ
0
), N
0
−
=
1
6
hv
0
iτ
0
S n
0
(x + λ
0
),
S
hv
0
iτ
0
S
J
x
= −
1
6
hv
0
i[n
0
(x + λ
0
) − n
0
(x −λ
0
)] .
1/6
1/6 x
x
n
0
(x + λ
0
) − n
0
(x −λ
0
) ≈ 2λ
0
dn
0
dx
.
D =
1
3
λ
0
hv
0
i.
1/3
D ∼
T
3/2
p
.
n p = nkT
σ
dT/dx
T
1
T
2
6= T
1
σ T